Application of a tailor-made polymer as a selective and sensitive colorimetric sensor for reliable detection of trace levels of uranyl ions in complex matrices1. Issue 74 (13th August 2015) - Behbahani, Mohammad; Salimi, Sara; Abandansari, Hamid Sadeghi; Omidi, Fariborz; Salarian, Mani; Esrafili, Ali
<x xml:space="preserve">Abstract</x> In this study, a new colorimetric chemosensor based on ion imprinted polymer nanoparticles was designed for quantitative detection of uranyl ions at trace levels in environmental water samples.